БЕРДАҚ ШЫҒАРМАЛАРЫНДА МИЙНЕТ ТЕМАСЫНЫҢ ЖЫРЛАНЫЎЫ - Давлетов, Барлықбай Абдимуратович (ILIM hám JÁMIYET, 2026)
The article highlights the interpretation of the theme of labor in the works of the poet Berdakh. The songs "When Will You Enjoy It", "For the People", "Better" were selected as the object of the research. The praise of labor, the value of industriousness, and the fact that honest labor is a force that leads to happiness are analyzed based on examples.